Sustainability of global Golden Inland Waterways - Yichu Wang (Nature Portfolio, 2020)
The exploitation of rivers has been at the detriment of river ecosystems. Here the authors propose a concept of Golden Inland Waterways (GIWs) to represent large waterways and find that the exploitation ratio threshold around the turning point for most GIWs appear to be less than 80%, subject to ecological constraints.